Analysis of the relationship of waste recycling to sustainable development objectives 2015-2030 - سلوم تأميم محمد; نور خليل ابراهيم (Journal of Economics and Administrative Sciences, 2020)
Waste recycling is one of the modern means of treating waste and minimizing its harmful effects that have caused problems for all countries of the world through the disposal of them in a safe and healthy manner as well as achieving economic and social benefits to the United Nations, and through the goals of sustainable development. 2015-2013 seeks to solve the environmental problems, including various peoples of the world, through various projects and programs, including waste recycling. Here is the question of whether there is a relationship between waste recycling and the goals of sustainable development, the research seeks to answer through five categories to determine the type of relationship between waste recycling and the goals of sustainable development (direct contribution, indirect contribution, achieving this goal contributes to the progress of recycling, opportunities, and initiatives that offer opportunities for recycling. The main results were that waste recycling has a relationship with 157 out of 169 targets, which contributes directly to the achievement of 32 sub-goals and indirectly contributes to the achievement of 23 sub-goals, and the most important recommendations were the need to adopt and support the policy of recycling waste to ensure the achievement of sustainable development goals 2015-2030.